Pengaruh Penambahan Asam Lemak Dalam Ransum Terhadap Kualitas Karkas Dan Irisan Komersial Karkas Ternak Potong - Yurleni, Yurleni; Priyanto, Rudi; Wirawan, Komang Gede (Fakultas Peternakan Universitas Jambi, 2016)
An experiment was carried out to investigate the effect of ration containing protected fatty acids on carcass quality and wholesale cuts of livestock. The protected fatty acids was in the form of dried carboxylate salt mixture (DCM). The experiments were assigned to 2x2 factorial model with two feeding treatment P0 (without DCM) and P1 (with DCM) and two animals types J0 (cattle) and J1 (buffaloes). The animals were slaughtered at 315.50±6.96 kg for buffaloes and 289,88 ±6.03 kg for cattle. The results showed that interaction was found between the two factors on striploin. DCM supplementation not significantly all parameters. The buffalo had significantly lower carcass percentage, loin eye area, tenderloin, silverside, fat colour score compared the cattle. It is concluded that DCM supplementation in the ration of buffalo cannot improve the quality of carcass and wholesale cuts. Keywords: carcass, wholesale cuts, buffalo, cattle, DCM.